2017
DOI: 10.4103/ijstd.ijstd_130_15
|View full text |Cite
|
Sign up to set email alerts
|

Correlating CD4 count with mucocutaneous manifestations in HIV-positive patients: A prospective study

Abstract: Background:Mucocutaneous findings may be the presenting symptoms in HIV-afflicted individuals. A multitude of mucocutaneous diseases also occurs during the course of the ailment, with some conditions being classed as disease defining. They include infectious diseases and noninfective inflammatory and neoplastic dermatoses. With progressive fall in CD4 count, there is a change in the types of mucocutaneous lesions encountered.Aim:This study aims to statistically correlate the CD4 counts with the mucocutaneous m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…A status of chronic immune inhibition, such as that seen in organ transplant recipients and patients with HIV/AIDS, hepatitis C virus, alcoholic pancreatitis or some malignancies, is associated with a much higher incidence of SD . The SD incidence in HIV‐positive patients have been reported as high as 30% to 83%, and later stages of HIV infection and decreased CD4‐positive T cell counts are often associated with more severe SD . These findings suggest that suppression of certain types of immune cells may render some other immune cells more active, which may facilitate the development of SD.…”
Section: Other Predisposing and Causative Factorsmentioning
confidence: 99%
“…A status of chronic immune inhibition, such as that seen in organ transplant recipients and patients with HIV/AIDS, hepatitis C virus, alcoholic pancreatitis or some malignancies, is associated with a much higher incidence of SD . The SD incidence in HIV‐positive patients have been reported as high as 30% to 83%, and later stages of HIV infection and decreased CD4‐positive T cell counts are often associated with more severe SD . These findings suggest that suppression of certain types of immune cells may render some other immune cells more active, which may facilitate the development of SD.…”
Section: Other Predisposing and Causative Factorsmentioning
confidence: 99%
“…Mucocutaneous manifestations are common in HIV infections and may sometimes be their earliest manifestations. A variety of skin disorders occur during the course of HIV, such as infectious skin diseases, noninfectious skin diseases, and malignant skin conditions [1]. It is reported that almost 90% of people living with HIV (abbreviated to PLHIV) will develop skin symptoms during the course of the disease [2].…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of DM was made for the first time in 8% of their patients by Verma and Celia et al found positive association between vulvovaginal candidiasis and diabetes mellitus. 13,14 In our study, none of the males were circumcised. Seven out of 12 diabetics had previously undetected diabetes and were diagnosed during evaluation for genital lesions.…”
Section: Discussionmentioning
confidence: 67%